ASUHAN KEPERAWATAN PADA Tn. A DENGAN GANGGUAN SISTEM ENDOKRIN DIABETES MELITUS TIPE II DENGAN MASALAH DEFISIT NUTRISI - Alda Nurzannah; Efi Irwansyah Pane (Jurnal Keperawatan Dan Kesehatan Holistik, 2025)
Type II Diabetes Mellitus is one of the endocrine system disorders characterized by chronic hyperglycemia due to insulin resistance and/or decreased insulin secretion. One of the common complications that often accompanies it is nutritional deficit, which has the potential to worsen the metabolic condition and quality of life of patients. This study aims to describe the nursing care provided to Mr. A, a patient with Type II Diabetes Mellitus who experiences nutritional deficit. The nursing process approach is used in the assessment, diagnosis, planning, implementation, and evaluation of nursing care. The main nursing diagnosis raised is nutritional deficit related to decreased food intake due to decreased appetite and metabolic disorders. Nursing interventions include monitoring nutritional status, providing education about diabetes diet, and psychological support to improve patient compliance and appetite. The evaluation results showed an increase in body weight, improvement in laboratory values, and an increase in daily food intake. Appropriate and collaborative nursing care can improve the nutritional status of patients with Type II DM, as well as prevent further complications. It is hoped that this case study can be a reference in clinical nursing practice, especially in treating patients with metabolic disorders and nutritional problems.